An intratesticular arteriovenous malformation identified incidentally during ultrasound evaluation of scrotal trauma - Jafarpishefard, Mohammad Saleh (Adv Biomed Res, 2016)
Intratesticular arteriovenous malformation (AVM) is an extremely rare benign testicular lesion. Ultrasonography (US) usually reveals a hypoechoic solid vascular mass within the testicular parenchyma. Herein, we report our experience with a young patient in whom an intratesticular AVM was found incidentally by US during the workup of scrotal trauma.